2006
DOI: 10.1097/00006231-200607000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and positive predictive value of CT, MRI and 123I-MIBG scintigraphy in localizing pheochromocytomas: A prospective study

Abstract: Our data suggest that this imaging protocol should be used in all patients with biochemically confirmed pheochromocytoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
1
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(65 citation statements)
references
References 21 publications
1
60
1
3
Order By: Relevance
“…Although MIBG scanning is reported to have a sensitivity of 83-100% in the detection of benign pheochromocytomas in case finding studies, this sensitivity is considerably reduced in familial, extraadrenal or malignant paragangliomas (Nielsen et al 1996, van der Harst et al 2001, Ilias et al 2003, Lumachi et al 2006. In our study, use of 123 I-MIBG for detection of intra-and extra-adrenal paragangliomas combined revealed a sensitivity of only 74% in our cohort with mostly familial paragangliomas.…”
Section: B Havekes Et Al: Screening In Sdhd Patientscontrasting
confidence: 58%
“…Although MIBG scanning is reported to have a sensitivity of 83-100% in the detection of benign pheochromocytomas in case finding studies, this sensitivity is considerably reduced in familial, extraadrenal or malignant paragangliomas (Nielsen et al 1996, van der Harst et al 2001, Ilias et al 2003, Lumachi et al 2006. In our study, use of 123 I-MIBG for detection of intra-and extra-adrenal paragangliomas combined revealed a sensitivity of only 74% in our cohort with mostly familial paragangliomas.…”
Section: B Havekes Et Al: Screening In Sdhd Patientscontrasting
confidence: 58%
“…Ninety-five percent of extra-adrenal pheochromocytomas are found in the abdomen and pelvis [79]. Both CT and MRI have a sensitivity of 98%-100% for adrenal pheochromocytomas [80], but MRI is more sensitive (94% versus 90%) for extra-adrenal pheochromocytomas [17,81,82]. Unfortunately, these tests have a specificity of approximately 70% because of the high incidence of adrenal incidentalomas [83].…”
Section: Imagingmentioning
confidence: 99%
“…The absence of ␤-emission and a shorter half-life result in a 20 times greater initial level of radioactivity administered to the patient without increasing the absorbed radiation dose, which accounts for the greater sensitivity of 123 I-MIBG [88]. In centers where this is not available, however, sitive agents include 18 F-fluorodeoxyglucose [90] and 82 rubidium [91], while more specific agents incorporate 11 C-hydroxyephedrine [92] and 6-18 F-fluorodopamine [87]. While studies have shown remarkably high sensitivity and specificity, the series are small and many of the agents are not yet in widespread clinical use.…”
Section: Imagingmentioning
confidence: 99%
“…Other studies had suggested the use of plasma-free metanephrines (99% sensitivity) or urinary-fractionated metanephrines (97% sensitivity) as the test of first choice for diagnosing pheochromocytoma [1,11]. CT scanning and MRI have similar sensitivities (> 90%) and specificities (79-80%) [1,17,18]. However, CT scan is still the method most commonly used to evaluate patients suspected of having adrenal pathology [19,20], and it is the preferred initial imaging modality in diagnosing pheochromocytoma in our centre.…”
Section: Discussionmentioning
confidence: 99%